(untitled) (Journal of Comparative & International Higher Education, 2024)
Panama’s Ministry of Education unnecessarily complicates its work with non-governmental entities, even when the entities are noted higher education institutions (HEIs). Bureaucratic impediments, lack of transparency and payment terms all present obstacles. During COVID-19, however, the crisis conditions and limited resources available propelled a period of streamlined public-private cooperation, resulting in some unparalleled innovation. This article presents a case study of one such HEI-ministry partnership on a digital transformation mobile literacy project, detailing its components and achievements and providing insights on specific success factors. Situating this discussion within the discourse on collaboration during crisis, the authors conclude that replicating and promoting this type of productive effort beyond periods of crisis will depend on public reform in two areas: (1) streamlining and professionalizing ministry-HEI interactions, and (2) increasing support for research and development, particularly in education. This discussion is relevant for Panama and most of Latin America as well as much of the developing world.